Intervensi Mengendalikan Tekanan Darah pada Pasien Hipertensi Melalui Pelatihan Relaksasi Otot Progresif Disertai Musik Klasik - Gultom, Agustina Boru; Batubara, Arbani (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Gunung Tinggi Health Center is located in Pancur Batu District, Deli Serdang Regency, where Hypertension was ranked 3rd of the 10 most common diseases in 2021. There are 2 working areas of the Gunung Tinggi Public Health Center which are still experiencing hypertension, including Sembahe Baru and Baru Village. The purpose of this activity was to increase knowledge about interventions to control blood pressure specifically through progressive muscle relaxation training accompanied by classical music, reducing stress and blood pressure in hypertensive patients. This community service used lecture, question and answer, demonstration and red-demonstration methods of providing interventions to control blood pressure through progressive muscle relaxation training accompanied by classical music, with a target of 60 hypertensive patients, carried out in two villages in the working area of ​​the Gunung Tinggi Health Center including Sembahe Baru Village and Baru Village each of 30 participants. The activities carried out included a pre-test for measuring knowledge, blood pressure and stress, followed by the provision of progressive muscle relaxation training interventions accompanied by classical music and ended with a post-test using the same questionnaire and tools. The results showed an increase in knowledge score of 25.58%, a decrease in stress of 33.94% and a decrease in systolic of 10.72 mmHg and a diastolic of 5.18 mmHg. Progressive muscle relaxation training intervention accompanied by classical music provides benefits in controlling stress, blood pressure and increasing knowledge.